Experimental Study Of SBPWM For Z-Source Inverter Five Phase - Mohd Shafie Bakar; Nasrudin Abd. Rahim; Hamdan Daniyal; Kamarul Hawari Ghazali (Institute of Advanced Engineering and Science, 2015)
On the basis of a conventional Z-source inverter, this paper presents an extension of the existing study about a driving scheme implementation of a simple boost pulse width modulation under open loop system for five phase two level system. The impact of design parameter (fixed modulation index and switching frequency) versus performance parameter (capacitor voltage, inductor current, total harmonic distortion and DC link voltage) are studied and analysed. To validate the advantages of Z-source five-phase inverter, the driving scheme are simulated using Matlab/Simulink and verified with real-time target board eZdspTM TMS320F28335. From the study, it was found that under specified modulation index and switching frequency, the THD of an output current fulfilled the EN61000-3-2 standard.